Household Factors and Gendered Education Gaps in Rural Kashmir - Gadda, Zakir Hussain; Jahangir, Mohmad Saleem (Voices of Teachers and Teacher Educators, 2025)
Relying on a qualitative research paradigm, this study explores the role of various household factors in school dropouts (Classes 1 to 10) among Muslim girls in rural areas of Kulgam district, Kashmir. The study consisted of 30 participants, from whom data was collected through in-depth semi-structured interviews. Their responses were subsequently analysed using Braun and Clark’s thematic analysis framework. The findings identified a range of multifaceted and interrelated household factors contributing to female school dropouts, including gender discrimination, poverty, patriarchy, a culture of illiteracy, increased workload and household structure. Additionally, concerns for daughters’ safety, family health issues, household conflicts and parental imprisonment were reported as contributing factors. Hence, policymakers and educationists are encouraged to raise awareness regarding the need and significance of educating girls, particularly in rural areas of Kashmir, to ensure equitable access to education.